Implementation of a webGIS service platform for high mountain climate research: the SHARE GeoNetwork project. (20th June 2014) - Locci, F.; Melis, M. T.; Dessì, F.; Stocchi, P.; Akinde, M. O.; Bønes, V.; Bonasoni, P.; Vuillermoz, E.
<x xml:space="preserve">Abstract</x> The implementation of a webGIS service platform dedicated to the management and sharing of climatological data acquired by high elevation stations is the core of the Station at High Altitude for Research on the Environment (SHARE) GeoNetwork project, promoted by the Ev‐K2 CNR Committee. The web platform basically will provide three types of services: structured metadata archive, data and results from high‐altitude environments research and projects; access to high‐altitude Ev‐K2 CNR stations and creation of a network of existing stations; dedicated webGIS for geo‐referenced data collected during the research. High elevation environmental and territorial data and metadata are catalogued in a single integrated platform to get access to the information heritage of the SHARE project, using open‐source tools: Geonetwork for the metadata catalogue and webGIS resources, and the open‐source Weather and Water Database (WDB), developed by the Norwegian Meteorological Institute, for the database information system implementation. The information system is designed to have a main node, with the possibility to install relocated subsystems based on the same technology, named focal point of SHARE, which will contain metadata and data connected to the main node. In this study, a new structure of metadata for the description of the climatological stations is proposed and WDB adaptation and data preprocessing are described in detail, giving code and script samples.